Adverse perinatal outcomes for advanced maternal age: a cross-sectional study of Brazilian births - Núbia Karla O. Almeida; Renan M.V.R. Almeida; Carlos Eduardo Pedreira (Elsevier, 2015)
ABSTRACT OBJECTIVES: To investigate the risk of adverse perinatal outcomes in women aged ≥41 years relatively to those aged 21-34. METHODS: Approximately 8.5 million records of singleton births in Brazilian hospitals in the period 2004-2009 were investigated. Odds ratios were estimated for preterm and post-term births, for low Apgar scores at 1 min and at 5 min, for asphyxia, for low birth weight, and for macrosomia. RESULTS: For pregnant women ≥41, increased risks were identified for preterm births, for post-term births (except for primiparous women with schooling ≥12 years), and for low birth weight. When comparing older vs. younger women, higher educational levels ensure similar risks of low Apgar score at 1 min (for primiparous mothers and term births), of low Apgar score at 5 min (for term births), of macrosomia (for non-primiparous women), and of asphyxia. CONCLUSION: As a rule, older mothers are at higher risk of adverse perinatal outcomes, which, however, may be mitigated or eliminated, depending on gestational age, parity, and, especially, on the education level of the pregnant woman.